Caretakers or HR Managers: The Role of HR Managers in Facilitating the Acquisition of Public Enterprises of Developing Countries by MNCs - Abugre, J.B. (My University, 2014)
Do human resources (HR) managers in developing countries have the clout to make strategic decisions during mergers and acquisitions (M&As)? This study aims at establishing the major roles played by HR managers in M&As of public sector companies in Ghana. The research examined the M&As of 10 Ghanaian companies where 10 HR managers gave detailed narratives of their roles and the part they played in the M&A processes. The qualitative method used to solicit the narratives of the HR managers resulted in the following findings: that HR managers in Ghana have a limited role in the planning process of the M&A; that indigenous HR managers perform several tasks in the course of the M&A to get employees stable before and after the M&A processes; nevertheless, they are not part of the policy formulators. The article makes a modest input of the significance of indigenous HR role in international M&As as a panacea to solving the global crises by advocating the empowerment of HR managers in developing context to be partners in the initial commencement of M&As.